PERANAN AUDITOR INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN - Erfiansyah, Erfan; Kurnia, Ia (2018)
This study aims to research the role of internal auditor to the quality of financial reporting. Financial reporting is an important part as consideration to make a decision. Therefore, the quality of financial reporting needs to be observed because it affects stakeholders’ decision. Nowadays, the role of internal audit is highlighted as one of the important roles to improve the quality of financial reporting. This study uses primary data by questionnaires given to the internal auditor of BPR in some areas of Bandung City, Bandung District, and West Bandung District. The sampling method used is purposive sampling. This research uses 33 samples of BPR with 60 internal audit respondents, and there are 50 questionnaires which were returned. Data analysis tool used is a simple linear regression. Before being tested using simple linear regression, testing the validity and reliability of the questionnaires that are used will be carried out. The results of this research shows that the internal auditor has a positive and significant role on the quality of financial reporting with the results by 62.4%. This figure means that 62.4% has strong enough influence. The more the internal auditor involves in monitoring the reliability of financial reporting, the better quality of financial reporting will be.